2011
DOI: 10.5430/ijfr.v2n1p31
|View full text |Cite
|
Sign up to set email alerts
|

Bank Size, Functional Distance and Loss Given Default Rate of Bank Loans

Abstract: Most of the studies available on relationship lending focuses on the benefits for borrowers and neglects those achievable for banks. In particular, empirical studies on the benefits achieved for banks in terms of loans recovery rate, in connection with loss given default rate, are very few. In contrast, choosing the best approach to managing loans is crucial in the current credit market considering the high deterioration in quality of bank loans.
This paper empirically tests whether the banks more oriente…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…According to Das and Ghosh (2003), if the bank advances loans in a traditional geographical market where bank managers are familiar with their clients, problem loans can be kept under control, given that the adverse selection problem does not exist. However, Cotugno and Stefanelli (2011) revealed that extension of the branch network with more autonomy would reduce the default rate, as it reduces the functional distance of operations. As to Goetz, Laeven, and Levine (2016), geographic diversification of banks does not affect loan quality.…”
Section: Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Das and Ghosh (2003), if the bank advances loans in a traditional geographical market where bank managers are familiar with their clients, problem loans can be kept under control, given that the adverse selection problem does not exist. However, Cotugno and Stefanelli (2011) revealed that extension of the branch network with more autonomy would reduce the default rate, as it reduces the functional distance of operations. As to Goetz, Laeven, and Levine (2016), geographic diversification of banks does not affect loan quality.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Das and Ghosh (2003) had mentioned that problem loans can be kept under control considering the manager's familiarity of the geographical area of expansion. Similarly, Cotugno and Stefanelli (2011) mentioned that the lesser the functional distance among branches is, the stronger the bank's recovery ability is, and hence, a low default rate could be executed. Goetz et al (2016) were in the view that geographic expansion lowers bank risk by enabling banks to diversify their exposure to idiosyncratic local market risks.…”
Section: Effect Of Bank-specific Factors On Nplsmentioning
confidence: 99%
“…( ) in observing that Italian SMEs are less credit rationed if their banks make greater use of soft information in their lending technology ), and that independent local banks are better able to recover bad loans (Cotugno and Monferrà, ; Cotugno and Stefanelli, ). Thus, functional distance may adversely affect bank performance, which is supported by Torluccio et al ( ) as well.…”
Section: Review Of Connected Literaturementioning
confidence: 99%
“…It is well-recognized that retail banking technology choices of human resource management relative to information technology system management are related to relationship lending issues that we are silent on. See, for example, Cotugno and Stefanelli (2011) for relationship lending focusing on the benefits for banks.…”
Section: Notesmentioning
confidence: 99%